PENGARUH BIMBINGAN KLASIKAL TERHADAP KONSEP DIRI SISWA DI SMP NEGERI 42 PEKANBARU - Dinda Maharani; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstact: Classical guidance is a service that is carried out in a face-to-face classroom provided by a counseling teacher or counselor to a number of students through activities or activities that take advantage of class activities. The research entitled the effect of classical guidance on students' self-concept aims to determine the differences and the effect of classical guidance on students' self-concepts. This type of research is experimental research. The research subjects were 40 students of class VIII. The instrument used is a self-concept measurement scale. This study uses a parametric statistical test using the formula paired sample t-test and simple linear regression test. For analysis using SPSS version 20. The results showed a significant influence classical guidance on students' self-concept.Key Words: Classical Guidance, Self Concept